Movement-dependent central processing of visual feedback for self-motion estimation in Drosophila melanogaster - Erginkaya, Mert (2022)
"Sensory experience critically depends on our own movement: The brain must incorporate information about self-movement to guide behavior, or discount self-generated sensory signals to detect external events in the world. How do sensory circuits process self-generated signals in different ways to meet specific demands?(...)"